Experimentation with psychoactive substances by public school students - Maria Eliane de Andrade; Igor Henrique Farias Santos; Antônio Araújo Menezes de Souza; Aliane Caroline Santos Silva; Tatiane dos Santos Leite; Cristiane Costa da Cunha Oliveira; Ricardo Luiz Cavalcanti de Albuquerque Júnior (Universidade de São Paulo, 2017)
ABSTRACT OBJECTIVE To analyze the prevalence of exposure to psychoactive substances in public students of basic education and its association with sociodemographic characteristics. METHODS This is a cross-sectional survey conducted from March to September 2015, involving 1,009 students of the basic and high school education in 20 public schools in the municipality of Aracaju, State of Sergipe, Brazil. The data have been compiled using questionnaires previously applied in national studies of the Brazilian Center for Psychotropic Drugs. The variables have been dichotomized for later logistic regression using the Chi-square test to analyze associations between experimentation with psychoactive substances and other sociodemographic variables; odds ratio and confidence intervals have also been calculated. The level of significance adopted was 5%. RESULTS We have identified that 69.6% of the students have experimented alcohol and 12.4% cigarettes. Age (≥ 15 years) has shown a significant association with experimentation with alcohol (p < 0.001) and cigarettes (p = 0.02), acting as risk factor in both cases (OR = 2.34 and 1, 78, respectively), but it acted as a protective factor for the use of inhalants (p = 0.03 and OR = 0.58) and weight loss medication (p = 0.006 and OR = 0.44). Religious practice had a significant association with experimentation with alcohol (p = 0.01), functioning as a protective factor (OR = 0.56). CONCLUSIONS We have concluded that the psychoactive substance most experienced by students was alcohol, followed by cigarettes, and chance for experimentation increases after the age of 15. Religious practice, in turn, acts as a protective factor for experimentation with alcohol.